Gut-Lung Axis in COVID-19 - Allali, Imane; Bakri, Youssef; Amzazi, Saaïd; Ghazal, Hassan (Interdisciplinary Perspectives on Infectious Diseases, 2021)
COVID-19 is a pandemic infection of the respiratory system caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The viral ribonucleic acid (RNA) was found in many parts of the COVID-19 patients including the stool, suggesting a potential interaction with the host’s gut microbiome. The gut microbiome also plays major roles in immunity and inflammation. It also impacts pulmonary functions through the gut-lung axis. There have been recent reports of the importance of the host microbiome in infection and pathogenicity. The understanding of the gut and lung microbiomes would open the gate to new therapeutic approaches.